Effect of open vs. closed kinetic chain exercises in ACL rehabilitation on knee joint pain, laxity, extensor muscles strength, and function: a systematic review with meta-analysis - Pamboris, George M.; Pavlou, Kyriakos; Paraskevopoulos, Eleftherios; Mohagheghi, Amir A. (Frontiers in Sports and Active Living, 2024)
Anterior cruciate ligament (ACL) injuries are common among active individuals, often requiring ACL reconstruction (ACLR) for recovery. Rehabilitating these injuries involves determining the appropriate timing for initiating open kinetic chain (OKC) exercises. While OKC exercises are effective post-ACLR, their use in rehabilitation remains debated. Therefore, the aim of this study was to conduct a systematic review to determine whether OKC or closed kinetic chain (CKC) exercises result in differences in laxity, strength of the knee extensor muscles group, function and functional performance in ACL rehabilitation. Five electronic databases were searched for randomized controlled between-group trials (RCTs). Two reviewers independently evaluated the risk of bias using the PEDro scale. We performed a meta-analysis using a random effects model or calculated mean differences (fixed-effect) where appropriate. Certainty of evidence was judged using the GRADE approach. The systematic literature search yielded 480 articles, of which 9 fulfilled the inclusion criteria. The evidence for all outcomes was very low to low certainty. Across all comparisons, inconsistent results were found in outcome measures that dealt with knee function between OKC and CKC exercises in post-ACLR. A significant increase in quadriceps isokinetic strength was found in post-ACLR and ACL-deficient knees in favour of OKC exercises at 3 (p=0.03) and 4 (p=0.008) months, respectively. A significant decrease in knee laxity was observed in ACL-deficient knees in favour of OKC at 10 weeks (p=0.01), although at 4 months presented inconsistency. Finally, a significant decrease in pain was found in favour of early, compared to late OKC (p<0.003). Additionally, in ACL-deficient knees, low load resistance training (LLRT) OKC showed no significant laxity difference compared to controls (p>0.05). In contrast, high load resistance training (HLRT) OKC had less laxity than controls at 6 weeks (p=0.02) but not at 12 weeks (p>0.05). OKC exercises appear to be superior to CKC for improving quadriceps strength 3-4 months after injury, either as a part of conservative or post-surgery rehabilitation. On the other hand, OKC exercises seem to be either superior or equally effective to CKC for improving knee laxity, thus presenting their importance in being included in rehabilitation protocols from the initial phase.